Turkish Water Policy And its impact on the Iraqi water intake - محمد, رشيد سعدون; مهدي, وسام وهيب (Al-Adab Journal, 2018)
The joining water considered the bigger challenge specially with the increasing of population and comprehensive development so it causes a stress on this case it causes increasing of the amount of poliutions in these rivers . The main factor in creasing of the climatically changes which in decrease of rainfalls in supply water . Every state have its own policy considers it a reason for this use , But when the foreign policy plays a great role in this effect it may be causing a positive side and this case is refuses by laws an norms , in the case perhaps it causes are flection specially the regions which have a shortage of water a mounts as it is in middle fast and Iraq is the most effected by policy specially it depends on a ratio about 53% from water outside its boarders .Turkey is the main supplying of water by Tigris and Euphrates this case reflecting on Iraqi actual and many irrigation Agricultural and developing projects which stopped , so water became a bigger challenge . For the sake of permanent these agreements Iraq tried pleasing Turkey state by economic investment in which exceeded 21 Millyar Dolor every year , But Turkey remaining to a chives its projects without pay attention with Basin states